Do measurements of inflammatory mediators in blood predict recurrence in patients with bisphosphonate-related osteonecrosis of the jaws?. Issue 3 (April 2016) - Mücke, Thomas; Jung, Maximilian; Mitchell, David A.; Wolff, Klaus-Dietrich; Wagenpfeil, Stefan; Stockmann, Philipp; Kesting, Marco Rainer; Deppe, Herbert
Abstract: Bisphosphonate-related osteonecrosis of the jaws (BRONJ) is well-recognised, difficult to manage, and often recurs. The aim of this study was to examine the value of preoperative measurements of inflammatory mediators in blood in 212 patients with BRONJ who were studied prospectively. Multiple logistic regression analysis was used to assess the importance of the amounts of substances in the blood that are independently associated with the dependent variable "recurrence of BRONJ". The only factor that significantly influenced the development of recurrent BRONJ was reduction in the white cell count (p<0.0001; hazard ratio 5.324; 95% CI 2.373 to 11.945). Neither white cell counts nor C-reactive protein concentrations within or above the reference ranges were significantly associated with recurrent BRONJ. Patients whose white cell counts were lower than the reference range were at increased risk of recurrent BRONJ. This may be a marker of reduced immunocompetence, and additional prophylactic measures or treatment should be considered for these patients.